The Wishing Spell: Book 1 (The Land of Stories) - Colfer, Chris (London Little, Brown Books for Young Readers, 2017)
Alex and Conner Bailey's world is about to change. When the twins' grandmother gives them a treasured fairy-tale book, they have no idea they're about to enter a land beyond all imagining: the Land of Stories, where fairy tales are real. But as Alex and Conner soon discover, the stories they know so well haven't ended in this magical land - Goldilocks is now a wanted fugitive, Red Riding Hood has her own kingdom, and Queen Cinderella is about to become a mother!